(untitled) (European Journal of Teaching and Education, 2023)
The concept that learners’ first language (L1) influences their second language (L2) acquisition and production is employed in a variety of studies on English language learners.However, so far, no research has been carried out on the Armenian learners of English. The fundamental question that this paper tries to answer is whether these theories apply for Armenian learners too, considering the specific features of the Armenian language. To this end I have identified the use pattern of the passive voice by Armenian learners in contrast to native speakers, aiming at revealing the influence of the Armenian language. The research is based on the contrastive interlanguage analysis of native speakers’ corpora (LOCNESS) and Armenian learners’ corpora (compiled by me in accordance with ICLE guidelines). The results yielded suggest that the pattern of Armenian learners’ use of the passive voice is drastically different from the native ones’ and that their L1 did have an impact on their production of passive voice.